2022
DOI: 10.1038/s42005-022-00833-2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization-driven Lifshitz transition and charge-spin coupling in the kagome metal YMn6Sn6

Abstract: The Fermi surface (FS) is essential for understanding the properties of metals. It can change under both conventional symmetry-breaking phase transitions and Lifshitz transitions (LTs), where the FS, but not the crystal symmetry, changes abruptly. Magnetic phase transitions involving uniformly rotating spin textures are conventional in nature, requiring strong spin-orbit coupling (SOC) to influence the FS topology and generate measurable properties. LTs driven by a continuously varying magnetization are rarely… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…After the compounds with a linked kagome lattice are excluded, the majority of remaining compounds satisfies our expectations based on their t value: compounds for which t is less than 1.4 have some clean or filled kagome bands, while compounds with t greater than 1.4 have no kagome bands. The commonly studied kagome compounds belong to a handful of structure types in these space groups (Figure S12), such as Ni 3 Pb 2 S 2 type in the space group , and CoSn, , MgFe 6 Ge 6 , and Co 3 GdB 2 , types in the P 6/ mmm space group. Both structure types of the hexagonal Laves phases, MgZn 2 and MgNi 2 , belong to the P 6 3 / mmc space group (Figure S12).…”
Section: Resultsmentioning
confidence: 99%
“…After the compounds with a linked kagome lattice are excluded, the majority of remaining compounds satisfies our expectations based on their t value: compounds for which t is less than 1.4 have some clean or filled kagome bands, while compounds with t greater than 1.4 have no kagome bands. The commonly studied kagome compounds belong to a handful of structure types in these space groups (Figure S12), such as Ni 3 Pb 2 S 2 type in the space group , and CoSn, , MgFe 6 Ge 6 , and Co 3 GdB 2 , types in the P 6/ mmm space group. Both structure types of the hexagonal Laves phases, MgZn 2 and MgNi 2 , belong to the P 6 3 / mmc space group (Figure S12).…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the spin structure changes in YMn 6 Sn 6 can induce multiple topological transitions [148]. Significant THE was observed in the TCS state [89,91] (figure 7(c)).…”
Section: Topological Hall Effect and Emergent Inductancementioning
confidence: 97%
“…As the topological band structures are determined by the magnetic order of R166, it can be effectively modulated by an external magnetic field as well. Currently relevant research mainly focuses on YMn 6 Sn 6 where the Mn spin is in an incommensurate flat spiral configuration and can be gradually aligned by an external field [89,91,109,148]. In an inplane magnetic field, the continuously varying spin structures may change the Fermi surface topology, causing a Lifshitz transition and a sharp reduction of the magnetoresistance up to 45% [148].…”
Section: Topological Band Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Mineral jarosite is the first kagome compound which has been experimentally found [3]. The kagome lattice exhibits interesting electronic properties due to its unique geometric arrangement [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The family of ternary transition metal chalcogenides, represented by the formula A 2 M 3 X 4 (where A are K, Rb, Cs; M are Ni, Pd, Pt; and X are S, Se), is commonly found to exhibit various crystal symmetries [20].…”
Section: Introductionmentioning
confidence: 99%